Site assessment for a small-scale Javan rusa (Rusa timorensis) captive breeding in East Java, Indonesia - SUBENO SUBENO; SATYAWAN PUDYATMOKO; MUHAMMAD ALI IMRON; TRI SATYA MASTUTI WIDI (Society for Indonesian Biodiversity, 2023)
Abstract. Subeno, Pudyatmoko S, Imron MA, Widi TSM. 2023. Site assessment for a small-scale Javan rusa (Rusa timorensis) captive breeding in East Java, Indonesia. Biodiversitas 24: 4568-4576. Javan deer (Rusa timorensis Blainville, 1822) is a protected wild animal with high potential economic value; captive breeding can be done to avoid extinction and sustainably utilize it. Most land ownership by rural communities in Indonesia is less than 5 ha; therefore, it is essential to design small-scale captive breeding, which local people can adopt to meet economic isxadwnterests and species conservation. We assessed a site part of the Perum Perhutani area in East Java dedicated to developing captive breeding models. Assessment is an essential consideration in exploring location feasibility and designing optimal allocation of available space; data collection on bio-physical conditions used nested sampling, circular plots, and profile diagrams. Feed availability is obtained by identifying the grass type and calculating its productivity. The collected data were then analyzed and compared with the needs of the Javan deer. The selected location was then made a captive design for space allocation based on the management and basic needs of the Javan deer. The results showed that the location at RPH (Resort Pemangkuan Hutan=Forest Management Resorts) Malo (Bojonegoro District, East Java, Indonesia) could be declared feasible to be developed as a Javan deer breeding area. The captive site design is mini ranching; this captive design consists of the breeding/management and office blocks.